2017
DOI: 10.1111/cobi.12905
|View full text |Cite
|
Sign up to set email alerts
|

Habitat as a mediator of mesopredator‐driven mammal extinction

Abstract: A prevailing view in dryland systems is that mammals are constrained by the scarcity of fertile soils and primary productivity. An alternative view is that predation is a primary driver of mammal assemblages, especially in Australia, where 2 introduced mesopredators-feral cat (Felis catus) and red fox (Vulpes vulpes)-are responsible for severe declines of dryland mammals. We evaluated productivity and predation as drivers of native mammal assemblage structure in dryland Australia. We used new data from 90 site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Responses of mammalian carnivores to agricultural lands vary, depending not only on the type of cultivar and the amount and configuration of native vegetation remaining in the matrix, but also on the ecology of each species [ 1 – 3 ]. Species responses to land conversion resulting in differential habitat use may modulate intra/interspecific interactions, and thus influence the effect of the species on other tropic levels [ 4 6 ]. Given that predators play critical roles in ecosystem structure and function [ 7 ], devising land management strategies for carnivore conservation in agricultural landscapes requires investigations of habitat use on each carnivore species in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Responses of mammalian carnivores to agricultural lands vary, depending not only on the type of cultivar and the amount and configuration of native vegetation remaining in the matrix, but also on the ecology of each species [ 1 – 3 ]. Species responses to land conversion resulting in differential habitat use may modulate intra/interspecific interactions, and thus influence the effect of the species on other tropic levels [ 4 6 ]. Given that predators play critical roles in ecosystem structure and function [ 7 ], devising land management strategies for carnivore conservation in agricultural landscapes requires investigations of habitat use on each carnivore species in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Hradsky et al ., ; Paschoal et al ., ). We've recorded a higher exotic predator occupancy in more degraded sites (Farris et al ., ), suggesting that as habitat degradation increases, native species face decreased habitat quality and increased exotic predator presence, which can amplify negative effects on native species (Brook, Sodhi & Bradshaw, ; Anson et al ., ; Doherty et al ., ; McDonald et al ., ). As primary rainforest becomes further degraded and exotic predators increase their presence in the region, it is entirely possible that native species populations will show intense declines.…”
Section: Discussionmentioning
confidence: 97%
“…In the context of the AWT, higher ruggedness values are likely indicative of boulder fields and steep drop‐offs in the environment. Most previous studies in Australia concluded that feral cats avoid topographically complex areas due to a reduction in hunting success in more structurally complex habitats (Hohnen et al, 2016; McDonald et al, 2017; McGregor, Legge, Potts, et al, 2015; McGregor et al, 2014). Due to sparse literature on feral cat ecology in rainforests, we can only hypothesize why feral cats in our study system might prefer more topographically complex terrain.…”
Section: Discussionmentioning
confidence: 99%